Reconstruction of Rights Based AI Governance: Right to Explanation Against Algorithmic Discrimination in ASEAN - Lisa Indahsari; Vebri Wulandari; Syafri Hariansyah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The rapid proliferation of artificial intelligence across Southeast Asia carries profound implications for the protection of fundamental human rights, particularly as algorithmic discrimination becomes increasingly embedded within automated decision making systems spanning public and private sectors alike. Although several ASEAN member states have issued AI ethics guidelines, the prevailing soft law framework has demonstrably failed to provide meaningful, enforceable protection for individuals subjected to biased and opaque algorithmic decisions. This study aims to critically examine the extent to which existing AI ethics guidelines in ASEAN fall short in mitigating algorithmic discrimination risks, and to reconstruct AI governance policy through the formal recognition of the right to explanation as a binding human rights protection instrument. Employing a normative juridical methodology, the research integrates a statute approach, comparative legal analysis, and conceptual framework analysis to systematically evaluate current regulatory inadequacies. The findings reveal that ASEAN's AI ethics guidelines remain largely voluntary, lack enforceable accountability mechanisms, and fundamentally fail to meet adequate standards of algorithmic accountability. A rights based reconstruction centered on the right to explanation anchored by a human understandable explanation standard as a prerequisite for the legitimacy of automated decisions represents a transformative normative shift from soft law to rights based AI governance. This study urges ASEAN to adopt a binding regional AI regulatory framework that guarantees accountability, transparency, and the protection of citizens' fundamental rights in the age of automation.